A novel Mxene-SPR-based sensor for sensing different types of cancers - Tene, Talia; León, Marcelo; Cevallos, Yesenia; Vinueza-Naranjo, Paola Gabriela; Inca, Deysi; Boukerche, Said; Vacacela Gomez, Cristian (Frontiers in Medicine, 2025)
Early-stage cancer screening benefits from optical transducers capable of reading minute refractive-index deviations in biofluids. This work models a surface-plasmon-resonance (SPR) biosensor that stacks copper, silicon nitride, and MXene in Kretschmann geometry and evaluates its response to six tumour-related refractive-index increments (Δn = 0.014–0.024 RIU). Transfer-matrix calculations guide a layer-by-layer optimisation: 40 nm Cu, 7 nm Si₃N₄, and two MXene sheets form the best-balanced configuration (Sys₃), while a single MXene layer on 45 nm Cu (Sys₄) offers an alternative with lower optical loss. The optimised MXene sensors raise angular sensitivity to 254° RIU−1 (Sys₃) and 312° RIU−1 (Sys₄) for the breast-T2 model, more than doubling the response of a dielectric-only stack and approaching values reported for multi-metal reference designs. Quality factors range from 48 to 58 RIU−1 in Sys₄ and 30 to 35 RIU−1 in Sys₃, corresponding detection limits fall near 2 × 10−5 RIU, sufficient to resolve the smallest Δn in the cancer panel. Optical loss remains below 9% in Sys₃ and under 8% in Sys₄, preserving reflected-intensity contrast for angle tracking. These results indicate that a copper platform augmented with sub-nanometre MXene and a thin Si₃N₄ spacer can match state-of-the-art sensitivity while relying on a single plasmonic metal and low-temperature fabrication. The study is purely theoretical and uses bulk refractive-index shifts as the sensing mechanism, future work should address surface chemistry, fabrication tolerances, and clinical validation.